2003
DOI: 10.1128/jb.185.15.4483-4489.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Psychrophilic and Thermolabile l -Threonine Dehydrogenase from Psychrophilic Cytophaga sp. Strain KUC-1

Abstract: A psychrophilic bacterium, Cytophaga sp. strain KUC-1, that abundantly produces a NAD ؉ -dependent L-threonine dehydrogenase was isolated from Antarctic seawater, and the enzyme was purified. The molecular weight of the enzyme was estimated to be 139,000, and that of the subunit was determined to be 35,000. The enzyme is a homotetramer. Atomic absorption analysis showed that the enzyme contains no metals. In these respects, the Cytophaga enzyme is distinct from other L-threonine dehydrogenases that have thus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 26 publications
(28 reference statements)
2
33
0
Order By: Relevance
“…6). Previous work showed that NAD ϩ binds to the active site prior to L-Thr and that the product, 2-amino-3-keto butyrate, is released before NADH (11). Data summarizing these changes are shown in Table 3.…”
Section: Molecular Dynamics Simulation Of Cnthrdh (Holo With Nadmentioning
confidence: 96%
See 1 more Smart Citation
“…6). Previous work showed that NAD ϩ binds to the active site prior to L-Thr and that the product, 2-amino-3-keto butyrate, is released before NADH (11). Data summarizing these changes are shown in Table 3.…”
Section: Molecular Dynamics Simulation Of Cnthrdh (Holo With Nadmentioning
confidence: 96%
“…More recently, Millerioux et al (12) demonstrated that SDR-like L-ThrDH is essential for lipid biosynthesis in Trypanosoma brucei, the causative pathogen of human African trypanosomiasis. The reaction catalyzed by SDR-like L-ThrDH proceeds via an ordered Bi-Bi mechanism; NAD ϩ binds to SDR-like L-ThrDH before binding of L-Thr, and the product 2-amino-3-keto butyrate is released before NADH (11). SDR-like L-ThrDH has higher substrate specificity for L-Thr than ADH-like L-ThrDH.…”
Section: The Atomic Coordinates and Structure Factors (Codes 3wmw Andmentioning
confidence: 99%
“…To investigate these alternatives, we used 3-hydroxynorvaline (3-HNV), a synthetic variant of threonine containing an extra carbon atom. The TDH enzyme can hydrolyze this threonine analog, yet instead of producing glycine and acetyl-CoA, catabolism of 3-HNVyields glycine and propionyl-CoA (11). Compared with the 3.56 mM K m (Michaelis constant) for threonine, the TDH enzyme catabolizes 3-HNV with a K m of 11.48 mM.…”
Section: Mouse Es Cells Critically Depend On Threoninementioning
confidence: 99%
“…Recently, a novel l ‐ThrDH that shows no sequence similarity to the E. coli enzyme was identified in a psychrophilic bacterium Flavobacterium frigidimaris KUC‐1 (formerly Cytophaga sp. KUC‐1) [12]. Characterization revealed the enzyme showed the V max / K m value for l ‐threonine at pH 9.0 and at 40 °C (64.5 U·mg −1 ·m m −1 ).…”
Section: Introductionmentioning
confidence: 99%